An Afropolitan 2017 update. Issue 2 (4th May 2017) - Morales, Donald
ABSTRACT: It has been over a decade since the publication of Taiye Selasi's essay "Bye Bye Babar" (2005) that viralized the term Afropolitan, engendering a controversy over its pros and cons. Yet the debate over the Afropolitan/Afropolitanism must resolve itself to art that is reflective and valid of the individual and his/her work at large, how transferable it is to the human experience and how it responds to where Africa's future fits into the grand scheme of things: "One must decide what comprises 'African culture' beyond pepper soup and filial piety" (Selasi, "Bye Bye Babar"). It must be remembered that Taiye Selasi's goal was to define a group of writers who reside in various capitals and whose works give a broader sense of who and what an African writer is.